Política pública de educação no contexto da Resex Médio Purus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The general objective of this research was to analyze the feasibility of the Public Education Policy within the scope of the Resex do Médio Purus, from the scenario of expansion of capitalism in the Amazon. To achieve this objective, the following specific objectives were defined: a) to characterize the scenario of expansion of capitalism in the Amazon; b) to identify the effects of its expansion on the way of life and education aimed at traditional peoples; c) to analyze the conditions for the feasibility of the public education policy in the Resex Médio Purus; and d) to understand the struggles and strategies of community leaders and the Deliberative Management Council of the Resex Médio Purus in relation to the fulfillment of the education policy. This study was guided by the following categories: Public Policies and Education. The research had as a theoretical and methodological contribution the historical- dialectical materialism. This is a field research carried out in 53 communities of the Médio Purus Extractive Reserve, with a qualitative approach, using the following instruments and techniques: bibliographic and documentary research, application of semi-structured interviews with the manager of the Médio Purus Extractive Reserve, coordinator of the Rural Schools, leaders, counselors, parents of students and teachers; notes in field notebooks, informal conversations, intensive direct observation and photographic records. From the analysis of the data, the modality of Extractive Reserve is recognized as a result of the long process of struggle of traditional peoples and social movements and emphasizes the permanent struggle for the implementation of public policies. Among these, the public education policy, which although it presents significant advances after the creation of the Resex Médio Purus and from the constant struggle for improvements in the quality of education, offered in the traditional communities of the Resex Médio Purus, still has many gaps and weaknesses in relation to what is recommended by the legislation regarding rural education. Such gaps are related to teacher training, teaching materials and methodologies for multigrade classrooms, differentiated calendar, school transportation, school feeding, partnerships between educational institutions, management body and communities.
Keywords: Comunidades - Amazônia; Ensino rural; Educação rural; CIENCIAS SOCIAIS APLICADAS: SERVICO SOCIAL; Comunidades tradicionais; Unidade de conservação; Educação do campo; Reserva extrativista